On the Predicament and Countermeasures of Agricultural Product Brand Construction in Cooperatives - Xiao, Mingqi (International Journal of Global Economics and Management, 2024)
Brand building of agricultural products can not only bring direct economic benefits to cooperatives, but also improve the internal environment of cooperatives through large-scale and standardized production and operation, as well as improve the external industry and market environment through regional brand building of agricultural products, while cooperatives can improve their own social service system in brand building. And promote the development of local tourism and service industry through the exploration and publicity of the cultural attributes of the brand. However, the brand construction of cooperative agricultural products is faced with many difficulties, such as weak brand awareness of members, lack of professional personnel, difficult quality and safety supervision under decentralized production and management mode and poor competitiveness of individual brands, outdated production and marketing mode, and imperfect financial services matching brand construction. This paper analyzes the difficulties encountered by cooperatives in brand building and puts forward construction measures, and holds that relevant departments should strengthen the cultivation of brand awareness of cooperatives; Cooperatives should increase the reserve and training of professional personnel, individual cooperatives should rely on the scale and resource advantages brought by regional brand building or association to carry out their own brand building, and at the same time use modern marketing means to expand their own sales channels; The government should regulate the operation of financial institutions and increase the popularity of agricultural insurance.